Livayi Divanı (metin-inceleme) - Seyhan, Köksal (My University, 2002)
Bu çalışmada eldeki iki nüshadan hareketle, Livâyî Divanı'nın tenkitli metni transkripsiyonlu olarak tespit edilmiştir. Giriş bölümünde Livâyî'nin yaşadığı dönem olan XVI. yüzyılda Osmanlı Devleti'inin siyasî durumundan ve divan edebiyatının önde gelen şairlerinden kısaca bahsedilmiştir. Dîvânının incelenmesiyle şair hakkındaki mevcut bilgiler arttırılmaya çalışılmış, hayatı değişik yönleriyle incelenmiştir. Kuloğlu olup bu sebeple yeniçeri olan, mîr-i alemliğe yükselen ve Şehzade Mustafa‰nın yanına görevli olarak gönderilen Livâyî‰nin, Şehzade‰nin katlinden sonra geçim derdiyle hattatlık yaptığını ve uzun bir ömür sürdüğünü tahmin etmekteyiz. Kalenderî olan ve bu tasavvufî düşüncelerini şiirlerinde başarıyla yansıtan şairin, bir de Kur‰an tefsiri bulunmaktadır. Farsça bildiği şiirlerinden, Arapça bildiği de yaptığı bu Kur‰an tefsirinden anlaşılan Livâyî, 16. yüzyılın iyi yetişmiş asker şairlerindendir. Divan, şekil, muhteva ve üslup açısından üç bölümde incelenmiştir. Şekil özellikleri kısmında divanda kullanılan nazım biçimleri, vezin, kafiye ve redif ile nüshanın imlâsı ele alınmıştır. Muhteva özellikleri bölümünde ilk olarak divandaki kasideler, musammatlar, gazeller ve kıtalarda işlenen konulara yer verilmiş, daha sonra şiirlerdeki ayet, hadis, peygamber ve din büyükleri olmak üzere dinî unsurlar gösterilmiş, son olarak da şeh-nâme kahramanları ve hikâye kahramanları tespit edilmiştir. Divandaki dil özellikleri, kullanılan atasözleri ve deyimler, ve şiirindeki belirgin olan özellikler tespit edilmiştir. Kendi şiiri hakkındaki düşünceleri, söz ve anlam sanatları ile Livâyî‰nin etkilendiği diğer şairler tespite çalışılarak şairliği değerlendirilmiştir. Bu incelemeyle elde edilen bilgiler sonuç kısmında değerlendirildikten sonra nüsha tavsifi yapılmış, metin tespitinde tutulan yol açıklanmıştır.

The aim of this study is to establish a critical edition and transliteration of Livâyî's Divan. In the introductory chapter a brief account is given of the political and historical events of the 16th century, corresponding to Livâyî's lifetime. A short survey of the achievements of the leading Divan poets who were his contemporaries has also been included. Since the data provided by the some biographies are very limited, an effort has been made to provide information of his life, based mainly on his own writings, namely the Divan. Born of a Janissary father, Livâyî himself became a Janissary by virtue of the Kuloğlu tradition, according to which a young orphan had the right to enter the ranks of the Janissaries upon the death of his father. Originally a standard bearer, he was promoted to leader of troops and was sent to Şehzade Mustafa in an official capacity. It is assumed that after Şehzade Mustafa was killed through conspiracy Livâyî worked as a calligrapher for his living. As a member of the Kalenderi sect, his mystical beliefs were reflected in the Divan. He also wrote a work which interpretated some sures of the Koran. His command of the Arabic and Persian languages shows that he was a well educated soldier-poet of the 16th century. The Divan has been studied with respect to its form, content and style. The section on form has focussed on the metre scheme, versification, rhyme and redif, together with the ortography of the text. In the section on content, space has been devoted primarily to the examination of the subjects treated in panegyrics (kasides), musammats, gazels, and stanzas. An analysis has been made of the use of motifs such as references to holy and religious figures, Koranic verses, hadiths, as well as mythological and legendary heroes, and the protagonists of popular romances. The study has, at the same time revealed the presence of allusions to contemporary figures, poets and events from daily life. The study of the stylistic features of the Divan has concentrated on linguistic characteristics, such as phraseology, the use of proverbial and idiomatic sayings and the employment of figures of speech and poetic artifices. Finally an attempt has been made to evaluate the achievements of Livâyî as a poet, based mainly on the quality of his compositions. A special section has been devoted at the end to the interpretation of textual characteristics and the exposition of the method used in editing the text.
Keywords: Divan Edebiyatı; Edebiyat; Osmanlıca edebiyat; Türk Dili Ve Edebiyatı